Microfluidic nanoparticle synthesis via continuous-wave laser heating - Mohammad, Laheji (2021)
Microfluidic nanoparticle synthesis has attracted significant attention in recent years, with several advantages over conventional batch synthesis: smaller concentration and temperature gradients, well-controlled and rapidly changeable reaction conditions, and easier scalability. Laser synthesis is a route that offers rapid formation of nanoparticles. Most works in the literature focus on laser ablation in liquids or thermal decomposition of gaseous precursors, but relatively little work has been reported on the decomposition of liquid precursors, most of which have no flow control. The possibility of combining these two synthesis methods is investigated in this thesis. This work presents a novel approach for nanocrystal synthesis within microfluidic chips, wherein thermal decomposition of metal organic precursors was achieved by localised laser heating using a continuous wave laser to produce iron oxide and cadmium selenide particles. As only the precursor solution was being heated, the chips could be made using inexpensive, commercially obtained acrylic.